A new modification of nanocomposite membrane permeation models: Consideration of sorption effects. (31st December 2020) - Nazari, Negin; Ghadiri, Mahdi
Graphical abstract: Highlights: A new approach was used to consider sorption effects in nanocomposite membrane modeling. An interface surface was suggested to predict sorption effects on prediction values. Mixed matrix membrane models were modified to model nanocomposite membranes. Four of the previously developed models were improved. Pressure effects on membrane permeation was investigated. Abstract: Permeation models were modified to determine the permeability of C3 H8, CH4 and H2 gases through the silica/PDMS nanocomposite membrane accurately. The average absolute relative error (AARE %) of permeation models is about 10–15% for low-sorbing gases of CH4 and H2 and approximately 30% for high-sorbing gas of C3 H8 . Furthermore, the gas solubility around the nanoparticles in the polymeric matrix is more than in the polymeric bulk due to sorption effects around the nanoparticles. Therefore, a new interface region is assumed to consider the sorption effects as a function of nanoparticle volume fraction and polymeric bulk permeability in the permeation models by genetic algorithm. It was found that the best-modified model for C3 H8 and H2 is Lewis–Nielsen and for CH4 is Bruggeman. Finally, the AARE values were obtained less than 5% for C3 H8 and less than 2% for CH4 and H2 that were in a good agreement with experimental data.